METODE KONTRASEPSI VASEKTOMI: PARTISIPASI PASANGAN USIA SUBUR DALAM PROGRAM KELUARGA BERENCANA DI KECAMATAN ABIANSEMAL BALI - Krisna Aditya, I Gusti Ngurah Agung; Zuryani, Nazrina; Suka Arjawa, I Gst.Pt. Bagus (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT Operational of family planning program that has been implemented leads women as target causes purpose of the International Conference on Population and Development in Cairo in 1994 that promote reproductive rights, women empowerment and gender equality has been agreed by all countries haven’t been achieve, one of them is implementation of men’s contraception. The research held from February-December 2014 applying observation, document study and photos, survey with questioners, and further interview. Lawrence Green’s Behavior Change Model showed policies that are enforced normatively by KBKS of Badung regency, differ with the existing situation. Highly knowledge of the respondents about method of vasectomy didn’t influence the decision to choose the contraception method. Awarding of money incentive and contraception services from PLKB and PKB didn’t give significant interest to respondents.The existence of Men Contraception Group was not optimal yet and testimony of experience from previous vasectomy acceptor didn’t interest to the respondents undergo surgery of vasectomy or join themselves to Men Contraception Group Kata kunci: Men, Participation, Vasectomy Contraception Method, Family Planning Program